Effect of Resveratrol on periodontal pathogens during experimental periodontitis in rats - Fabiano Ribeiro CIRANO; Renato Correa Viana CASARIN; Fernanda Vieira RIBEIRO; Marcio Zaffalon CASATI; Suzana Peres PIMENTEL; Tiago TAIETE; Maria Martha BERNARDI
Abstract The objective of this study was to investigate the antibacterial effect of resveratrol against putative periodontal pathogens during the progression of experimental periodontitis in rats. Periodontitis was induced in rats in one of the first molars chosen to receive a ligature. Animals were assigned to one of two groups: daily administration of the placebo solution (control group, n = 12) or 10 mg/Kg of resveratrol (RESV group, n = 12). The therapies were administered systemically for 30 days, for 19 days before periodontitis induction and then for another 11 days. Then, the presence and concentrations of Porphyromonas gingivalis, Tannerella forsythia and Aggregatibacter actinomycetemcomitans in the cotton ligatures collected from the first molars were evaluated using real-time PCR. Inter-group comparisons of the microbiological outcomes revealed that no differences were detected for P. gingivalis, T. forsythia and A. actinomycetemcomitans levels (p > 0.05). Continuous use of resveratrol did not promote additional benefits in microbiological outcomes during experimental periodontitis in rats.